Gender Differences in English for Nusantara VII Textbook - Jamilah, Sitti; Sabrina, Sabrina; Ismail, Nyak Mutia (Universitas Teuku Umar, 2024)
This study explores the representation of gender roles in the government-published English for Nusantara VII textbook for seventh-grade students, focusing on the portrayal of male and female characters in imagery and the actions they perform. Gender representation in educational materials is crucial, as it can shape students’ perceptions of societal roles. Despite efforts to promote gender equality in education, textbooks often exhibit gender biases, either by underrepresenting females or depicting them in stereotypical roles. This research addresses the gap in existing studies by examining the frequency and types of activities associated with male and female characters in the textbook. A content analysis method was used to quantify and analyze the presence and actions of male and female characters. The findings reveal a significant gender imbalance: male characters appeared more frequently and were often depicted in active, leadership, and outdoor roles, while female characters were more passive, engaging in stereotypically feminine tasks like reading and household chores. The implication of this study is that such gender biases in educational materials may reinforce traditional stereotypes, potentially influencing how students perceive gender roles in society. Addressing this issue is vital for promoting gender equality in education. Future research should explore the impact of these representations on students' learning and development, and seek to create more balanced and inclusive educational resources that challenge traditional gender norms.